NUANSA EDUTAINMENT DALAM PEMBELAJARAN KURIKULUM SD/MI 2013 - Agustia, Nanda Rahayu (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
The nuances of edutainment in the concept of learning in the 2013 SD/MI curriculum. This can be seen in the effort to create a conducive learning climate. Efforts to prepare classrooms that provide fun and not boring learning facilities, namely by using fresh flowers and various colors. The walls are decorated with various colorful posters and it is recommended to use music to create a conducive atmosphere. Furthermore, fun learning is a learning process that gives students the opportunity to play an active role. Learning must also prioritize interests, emotions and involve all the senses and minds of students in learning activities. The implementation of edutainment based learning in the 2013 SD/MI curriculum can be done with the following steps: first, creating an atmosphere that encourages students to be ready to learn, Second, recognizing students' learning styles. Third, apply active learning and Fourth, apply learning based on activities and thoughts.